Poetry, Religion, and Morals Essence - Relation and function - a reading in heritage - - boukafa, abd elmalek amine (Milev Journal of Research and Studies, 2015)
The subject of my article is the different artistic writings which harm religious feelings. In my article, I dealt with the attitudes of our critics about this topic, and I focused on Eldjordjani‘s quotation: “Poetry and religion are separated“. Through a deep understanding of this statement, I concluded that the aesthetic aspect of writings should not be at the expense of the cultural criticism of their content.